P7 Consumption of antioxidant-rich drinks does not protect against endothelial dysfunction associated with a high-calorie meal challenge. (May 2019) - Goszcz, Katarzyna; Muggeridge, David J; Crabtree, Dan; Treweeke, Andrew; Adamson, Janet; Hickson, Kirsty; Megson, Ian L
Abstract : Endothelial dysfunction is key factor in atherosclerotic cardiovascular disease. Post-prandial increase in glucose, triglycerides, fatty acids, protein and insulin leads to endothelial dysfunction and an increase in intracellular reactive oxygen species generation on account of metabolic overload has been implicated. Supplementation with vitamin C has been shown to reverse the negative effects of postprandial endothelial dysfunction, lending weight to the suggestion that oxidative stress might play a crucial role in induced endothelial dysfunction. The aim of this study was to test the hypothesis that co-consumption of antioxidant-rich drinks with a high-calorie meal ameliorates post-prandial endothelial dysfunction. This study was an open-label crossover design. 7 healthy volunteers (BMI 25–35; mean age 57±3 years; 1 male, 6 females) co-ingested a high-fat and high-carbohydrate meal (∼50 g, ∼35 g, respectively;≥900 kcal) with one of a range of drinks (250 ml) with different antioxidant profiles; water (control), orange juice, green tea or red wine. Endothelial function was measured immediately before (baseline) and 2 hours after the meal challenge by flow mediated dilatation (FMD) of the branchial artery. Additionally, various blood parameters including glucose, cholesterol, oxidised low density lipoprotein (oxLDL), triglycerides, ascorbate and oxygen radical antioxidant capacity (ORAC) were measured pre- and post- (2 hour) meal consumption. FMD results showed substantial decrease in endothelial function (∼−30%) 2 hour after the meal challenge. However, none of the antioxidant drinks protected against meal-induced endothelial dysfunction at this time point. Significant increase in triglycerides (≥100%, p<0.001), but not in glucose or cholesterol was also observed. There was no change in antioxidant capacity of plasma samples measured by ORAC and no change in plasma ascorbate. Interestingly, the plasma oxLDL concentration was not affected by the meal challenge either. In conclusion, none of the antioxidant drinks protected against meal-induced endothelial dysfunction. This, together with the lack of change in oxLDL concentrations or plasma antioxidant capacity, suggest that oxidative stress might not play a leading role in endothelial dysfunction at this time point and/or that co-ingesting antioxidant drinks with unhealthy meals is unlikely to prevent endothelial dysfunction in the acute phase. This study was part-funded by the BBC 'Trust me I'm a doctor' series. KG and DC are funded by Highlands and Islands Enterprise; DM is supported by the European Union's INTERREG VA Programme, managed by the Special EU Programmes Body (SEUPB).